(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
In the article are analyzed some ways of reception of substitutes of cocoa butter (SCB) from cotton saturated fat and palmitines. We made conclusion that during hydrogenation of cotton palmitin till fusion temperature 40-42 o C and, further, interesting the received saturated palmitin fat with received by priming palmitin, it is possible to receive SCB with fusion and hardening temperature of 36-37 o C and 27 -28 o C, accordingly.